1973
DOI: 10.1051/forest/19730201
|View full text |Cite
|
Sign up to set email alerts
|

Qualité du bois et largeur d'accroissements en forêt Tronçais

Abstract: RÉSUMÉUne étude portant sur 125 échantillons non destructifs récoltés dans 5 parcelles différentes et sur 740 éprouvettes normalisées a permis de mettre en évidence les résultats suivants :Quand on compare entre elles les valeurs moyennes des différentes parcelles, la densité du bois augmente avec la largeur des accroissements (du fait principalement d'un double gradient négatif lié à l'âge).A l'intérieur d'une même parcelle, il n'y a pas de liaison significative entre densité et largeur de cernes; il est donc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
19
0
8

Year Published

1978
1978
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 1 publication
3
19
0
8
Order By: Relevance
“…These findings corroborate Paul (1963) studies in unmanaged stands of Q. alba and Q. velutina, where the variation in density was significantly related to changes in ring width with increasing tree age as well as in managed stands (Zhang et al, 1993;Degron & Nepveu, 1996;Guilley et al, 1999). Zhang (1994) concluded that in ring-porous species, ring width had little influence on density while other studies refer to inconsistent relationships between ring width and wood density for other oaks (Polge & Keller, 1973).…”
Section: Rd Ewd Lwd Ewwsupporting
confidence: 82%
See 1 more Smart Citation
“…These findings corroborate Paul (1963) studies in unmanaged stands of Q. alba and Q. velutina, where the variation in density was significantly related to changes in ring width with increasing tree age as well as in managed stands (Zhang et al, 1993;Degron & Nepveu, 1996;Guilley et al, 1999). Zhang (1994) concluded that in ring-porous species, ring width had little influence on density while other studies refer to inconsistent relationships between ring width and wood density for other oaks (Polge & Keller, 1973).…”
Section: Rd Ewd Lwd Ewwsupporting
confidence: 82%
“…Therefore these species show a positive correlation between latewood proportion and ring width (Polge & Keller, 1973;Zhang et al, 1993). In the present study, this correlation was significant with a positive trend, showing that latewood width was proportional to total ring width.…”
Section: Rd Ewd Lwd Ewwsupporting
confidence: 66%
“…The high harvesting intensity has created canopy gaps and has stimulated a pulse beech establishment. The oak ring width is usually considered as a good indicator of wood quality because wood properties (density, shrinkage, machinability…) are closely correlated with ring widths [39][40][41]. Thus, wide rings (> 1.5-2 mm) correspond to denser wood which is less favourable to veneer production (the main use of oak wood) because denser wood in this species is associated with higher shrinkage and machinability [14,53,54].…”
Section: Discussionmentioning
confidence: 99%
“…Néanmoins, sur le plan économique, il apparaît que, pour de nombreuses essences et en particulier pour le chêne, les qualités externe et interne de la matière ligneuse produite prévalent sur la quantité (Polge et Keller, 1973 ;Normandin, 1990 ;Polge, 1990 (Ackermann, 1994b), avait déjà été abordé par de nombreux auteurs (Zahner, 1968 ;Le Tacon et Mormiche, 1974 ;Polge, 1973Polge, , 1975Courtoisier, 1976 ;Pellecuer, 1976 ;Becker, 1979 ;Mourey, 1979 ;Drapier, 1987 ;Klumpers, 1990 (Nepveu, 1992 (Nepveu, 1988(Nepveu, , 1989, 1992 (Polge, 1966 ;Nepveu, 1989 ;Zhang et al, 1994 …”
unclassified